Digital trigonometry module utilizing liveworksheet to enhance university students' mathematical communication skills - Edi Susanto; Dewi Rahimah; Effie Efrida Muchlish; Siti Rochana (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
Supporting the development of university students’ cognitive skills in higher education necessitates the design of instructional materials that cultivate critical thinking. Integrating technology into teaching resources has become prevalent in higher education, proving effective in advancing students' skills. This study aims to evaluate the validity of a digital trigonometry module based on LiveWorksheet, assess its practicality from the users' perspective, and determine its effectiveness in enhancing mathematical communication skills. The study follows a research and development with five phases: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Participants included two experts-one in mathematics education and another in ICT education and 62 students (Class A, n=32; Class B, n=30). These students were enrolled in a trigonometry course taught by the researcher. Data were gathered via questionnaires and mathematical communication skill assessments, with qualitative descriptive analysis used to address the research objectives. Results indicate that the digital trigonometry module meets established validity criteria. The implementation findings demonstrate that the module is both practical for users and effective in enhancing students' mathematical communication skills, with average student performance reaching a high level. These findings suggest that LiveWorksheet-based digital instructional materials, particularly when incorporating media such as videos and interactive quizzes, can significantly enrich learning support